SUMBANGAN PEMIKIRAN JOHN HICK BAGI PERJUMPAAN AGAMA-AGAMA - Agustinus A. Lopuhaha (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2018)
The thought developed by John Hick is one source of inspiration to develop religious patterns that humanize humans and have a peaceful face. The thoughts contained in this thought illustrate that all religions have the freedom to develop. This freedom base assuming all religions have their own way of salvation. The path of salvation is a manifestation of the expression and reaction of faith in God's revelation. The experience of conflict involving religious symbols is one of the fanatical attitudes of conventional interpretation of religious documents. John Hick gave a thought to make the facts that exist in each religion as a point to build dialogue. This refers to human values in every religion that must be upheld.Keywords: John Hick, Theocentric, Exclusive, Inclusive, Pluralist